2017
DOI: 10.5964/jnc.v3i2.64
|View full text |Cite
|
Sign up to set email alerts
|

Multiple skills underlie arithmetic performance: A large-scale structural equation modeling analysis

Abstract: Current theoretical approaches point to the importance of several cognitive skills not specific to mathematics for the etiology of mathematics disorders (MD). In the current study, we examined the role of many of these skills, specifically: rapid automatized naming, attention, reading, and visual perception, on mathematics performance among a large group of college students (N = 1,322) with a wide range of arithmetic proficiency. Using factor analysis, we discovered that our data clustered to four latent varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 50 publications
(76 reference statements)
1
6
0
Order By: Relevance
“…Consistent with previous studies [31,60], our results suggest that there is an interplay between different cognitive skills and executive functions and the level achieved in solving specific types of mathematical problems. Research has shown that working memory and inhibition, but not switching, are associated with individual differences in solving problems with whole numbers [26].…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with previous studies [31,60], our results suggest that there is an interplay between different cognitive skills and executive functions and the level achieved in solving specific types of mathematical problems. Research has shown that working memory and inhibition, but not switching, are associated with individual differences in solving problems with whole numbers [26].…”
Section: Discussionsupporting
confidence: 92%
“…First, this is not surprising because a high comorbidity of MLD and other developmental deficits such as dyslexia (Barbaresi et al, 2005;Gross-Tsur et al, 1996) or other cognitive deficit such as executive control impairment (Geary, Bailey, Littlefield, et al, 2009;Rotzer et al, 2009) has been frequently reported. Furthermore, Ashkenazi and Silverman (2017) recently indicated that multiple factors can affect mathematics performance (processing speed, perception, sustained attention, reading). In the present study, we adopted a practical selection procedure, which reflects the reality existing in clinical and school settings.…”
Section: Discussionmentioning
confidence: 99%
“…These consisted of multiple different measures (standardized to z scores), such as RT and accuracy rate (ACC) in the arithmetic tasks, or RT, RT variance, and error types (omission and commission) in the CPT task. Prior to the analysis, efficiency scores for each task were calculated (Ashkenazi & Silverman, 2017). For both arithmetic automaticity and procedural knowledge, efficiency scores were calculated by averaging the ACC and RT z score.…”
Section: Resultsmentioning
confidence: 99%
“…The test battery was developed by the Israeli National Institute for Testing and Evaluation in cooperation with the Israeli Council for Higher Education. The MATAL test battery includes 20 tests and 54 performance measures used to assess proficiency in mathematics, reading, writing, English (as a second language), and attention (for further information on the MATAL, see Ashkenazi & Silverman, 2017; Ben-simon et al, 2013; Goldfarb & Shaul, 2013; Mazor-Karsenty et al, 2015). All students were Hebrew speakers, diagnosed at the University of Haifa diagnostic center between the years 2010 and 2019.…”
Section: Methodsmentioning
confidence: 99%